2014
DOI: 10.1088/0963-0252/23/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

A nanosecond surface dielectric barrier discharge in air at high pressures and different polarities of applied pulses: transition to filamentary mode

Abstract: The development of a nanosecond surface dielectric barrier discharge in air at pressures 1-6 bar is studied. At atmospheric pressure, the discharge develops as a set of streamers starting synchronously from the high-voltage electrode and propagating along the dielectric layer. Streamers cover the dielectric surface creating a 'quasi-uniform' plasma layer. At high pressures and high voltage amplitudes on the cathode, filamentation of the discharge is observed a few nanoseconds after the discharge starts. Parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 31 publications
(44 reference statements)
8
109
0
Order By: Relevance
“…The thickness of the discharge in any of the considered experimental conditions did not exceed 0.5 mm. The third case (6 atm, −47 kV) was described for the first time in [20]. It was observed in air for negative polarity of the discharge with an increase of pressure or of the HV pulse amplitude.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The thickness of the discharge in any of the considered experimental conditions did not exceed 0.5 mm. The third case (6 atm, −47 kV) was described for the first time in [20]. It was observed in air for negative polarity of the discharge with an increase of pressure or of the HV pulse amplitude.…”
Section: Resultsmentioning
confidence: 92%
“…In the developed filamentation mode, one filament is created instead of four to six streamers, and the filamentation structure is very regular, as is represented in figure 5c. No temperature increase, either significant increase of electrical current or deposited energy, is detected at streamer-to-filament transition [20]. It was suggested that a physical reason for this 'single-shot' filamentation is the ionization-heating instability on the boundary of the cathode layer [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In nanosecond duration, negative polarity pulses (τ pulse << 100 ns), the generation of "negative sparks" appears unlikely. The work [21] discussed the transition of NS SDBD to a "filamentary" mode although it looks to be a different process than considered in the current paper. An analysis of the data collected by the charge sensors was used to quantify the effect of discharge contraction and waveform polarity on charge transfer and energy coupled.…”
Section: Single Polarity Waveformmentioning
confidence: 93%
“…Another prominent example of the generation of non-thermal plasmas are surface dielectric barrier discharges (SDBDs) [3]. Although SDBDs are commonly sine-driven it has been shown experimentally [4] that pulsed operation enables in a range of applications a higher yield of different species, lower power consumption and allows the study of variable HV parameters that define the discharge characteristics. The results of experimental investigation of pulsed driven SDBD can be used in modeling of the surface discharges for different conditions.…”
Section: Introductionmentioning
confidence: 99%